Recent Advances in Renal Denervation Therapy and Novel Applications of High-Intensity Focused Ultrasound - JunHao Wang (Cardiovascular Therapeutics, 2025)
Hypertension constitutes a major risk factor for cardiovascular diseases. Globally, the management and control of hypertension remain suboptimal. At present, pharmacological intervention is a critical strategy for patients with hypertension to achieve blood pressure regulation. Nevertheless, inadequate adherence to prescribed medication significantly impedes effective blood pressure control. Renal denervation (RDN) has emerged as a minimally invasive intervention that has the potential to achieve long-term reduction in blood pressure. Many preclinical and clinical trials have validated the effects of RDN. While trials such as SYMPLICITY HTN-3 raised questions about the efficacy of RDN, the majority of subsequent clinical trials have demonstrated benefits in patients with resistant hypertension. Presently, traditional RDN therapy is characterized by invasiveness and technical complexity, so the utilization of noninvasive high-intensity focused ultrasound (HIFU) has been incorporated into RDN procedures. This review is aimed at consolidating data on the efficacy and safety of various RDN modalities, examining the implementation of noninvasive HIFU in RDN practices, and suggesting potential avenues for future advancements and opportunities.